PENGARUH KONSENTRASI NaCl DAN VARIETAS TERHADAP VIABILITAS, VIGOR DAN PERTUMBUHAN VEGETATIF BENIH KACANG HIJAU (Vigna radiata L.) - Jasmi Jasmi (Universitas Teuku Umar, 2018)
The aims research were to know the effect of NaCl concentration and variety towards viability, vigor and vegetative growth of seeds of mung bean (VignaradiataL.), as well as it is not real interaction of these two factors. Experimental design used in this research is a complete Random Design (RAL) factorial pattern. Factors examined include the concentration of NaCl and varieties. The concentration of NaCl which consists of three levels: 1000, 2000 and 4000 ppm,and varieties consist of three levels, namely,walet, perkutut, and betet. The observed variables include the potential for power is growing, germinated, seed germination uniformity, growing speed, and high vigor and seedling plants and number of leaves at the age of 10, 20 and 30 HST. The results show is the concentration of NaCl real effect against a potential of growing and seedling vigor. Mung bean germination and vegetative growth is best found in the treatments with NaCl concentration of 1000 ppm/L water. While the real effect against to seed germination uniformity.The best germination and vegetative growth of mung bean plants found in perkututvarieties. There is no real interaction between the concentration of NaCl and varieties against a potential of growing power, germinate, grow, seed germination uniformity, vigor of seed sprouts green beans as well as the high number of plants and leaves of plant mung bean. Keywords: mung bean, NaCl concentration, viability, vigor